2018
DOI: 10.1016/j.bbabio.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation-driven mitochondrial hyperpolarization predicts insulin secretion in human pancreatic beta-cells

Abstract: Mitochondrial metabolism plays a central role in insulin secretion in pancreatic beta-cells. Generation of protonmotive force and ATP synthesis from glucose-originated pyruvate are critical steps in the canonical pathway of glucose-stimulated insulin secretion. Mitochondrial metabolism is intertwined with pathways that are thought to amplify insulin secretion with mechanisms distinct from the canonical pathway, and the relative importance of these two pathways is controversial. Here I show that glucose-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 89 publications
0
26
0
Order By: Relevance
“…Glucose-induced decrease in J m rates was also observed in the presence of etomoxir (Fig. 4A) (24), AOA (of a lower extent) ( Supplementary Fig. S2Cc), and when the malate/ aspartate shuttle (Fig.…”
Section: Mitochondrial Matrix Superoxide Release Is Attenuated On Tramentioning
confidence: 53%
“…Glucose-induced decrease in J m rates was also observed in the presence of etomoxir (Fig. 4A) (24), AOA (of a lower extent) ( Supplementary Fig. S2Cc), and when the malate/ aspartate shuttle (Fig.…”
Section: Mitochondrial Matrix Superoxide Release Is Attenuated On Tramentioning
confidence: 53%
“…Other studies have provided supporting evidence for ageassociated changes in important components of the stimulussecretion coupling mechanism, such as a decline in the coordination of calcium dynamics, gap junction coupling and insulin secretion with age in humans [11]. Another key player of insulin secretion is mitochondrial activity, which is impaired in aged human islets as measured by NADPH fluorescence lifetime imaging [10,23]. A study performed in single human beta cells suggested that the mechanistic deficit underlying changes in mitochondrial activity is located upstream of the citric acid cycle (CAC), thus altering the control of mitochondrial membrane potential [24].…”
Section: Mechanisms Of Insulin Secretion Change With Agementioning
confidence: 94%
“…As we demonstrated in INS-1E cells, expression of the DAPIT and other F O subunits determined the intensity of ATP synthesis. The latter is indicated by the V 3 / V 4 ratio, increases with the increasing glucose from insulin non-stimulating (3 mM) to insulin stimulating concentration (>8 mM) [ 11 , 12 , 14 , 15 , 16 ]. However, as we now show, this does not proceed in DAPIT-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another peculiar aspect of the pancreatic β-cell glucose sensor is the steepness of the related dose–response, i.e., insulin release dependence vs. glucose concentration [ 11 , 12 , 14 , 15 , 16 ]. The revealed narrowing of mitochondrial cristae may hypothetically contribute to this steepness, such as observed in INS-1E cells during GSIS [ 17 ] or upon the increased load of cell-permeant Krebs cycle substrate [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%